In Vitro and In Silico study on the interaction between apigenin, kaempferoland 4-hydroxybenzoic acid in xanthine oxidase inhibition - Chin, Yong Sin; Loh, Khye Er; Wee, Sze Ping; Ong, Ghim Hock (Penerbit Universiti Kebangsaan Malaysia, 2023)
Xanthine oxidase (XO) is a biological enzyme that takes part in purine catabolism. It catalyses the conversion of hypoxanthine to xanthine and eventually xanthine to uric acid. The catabolism reaction increases the level of uric acid and subsequently leads to hyperuricemia. Allopurinol is a XO inhibitor that is used clinically to prevent purine catabolism. Although it is an effective XO inhibitor, it causes some side effects. Therefore, a more effective inhibitor with fewer side effects is in an urgent need. Phenolic compounds have been identified as effective XO inhibitors in many studies. In vitro and in silico study were conducted to investigate the interaction between apigenin, kaempferol and 4-hydroxybenzoic acid in XO inhibition. Apigenin was found to be the most effective XO inhibitor among the compounds tested with the best docking score of -8.2 kcal/mol as demonstrated in the molecular docking simulation which indicated its favourable interaction with XO enzyme. Additive interactions between compounds namely apigenin-kaempferol, apigenin-4-hydroxybenzoic acid and 4-hydroxybenzoic acid-kaempferol were demonstrated in both in vitro and in silico studies. The results showed that 4-hydroxybenzoic acid- apigenin (-7.4 kcal/mol) was the most stable ligands combination docked to XO. The multiple ligands docking simulation showed independent ligands bound to the XO active site at non-interfering regional location. In conclusion, the combination of these three compounds can be explored further for their additive interaction in XO inhibition, which could be beneficial in terms of the enhanced effectiveness and lower side effects when each is used at lower dose to give the same effect.